2018
DOI: 10.1002/apj.2255
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sustained ciprofloxacin release of biodegradable electrospun gelatin/poly(glycerol sebacate) mat membranes for wound dressing applications

Abstract: In this research, gelatin and poly(glycerol sebacate) (PGS), which have demonstrated significantly developed wound healing process, were used to fabricate biodegradable and bioabsorbable membranes with controlled release of ciprofloxacin (CIP) as a powerful antibiotic. This was achieved by taking advantage of electrospinning technique to accelerate the wound healing as an extracellular matrix-liked composite membrane. We attempted to carefully investigate the impact of variable ratio of sebacic acid and glycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…After 14 days, the cells covered the scaffold surface and formed a tissue layer (not presented). Various studies have reported that the surface hydrophilicity serves an important role in the cell morphology on non-toxic materials, while the 24-50 degree of contact angle is a suitable range for cell attachment and proliferation (36,38). Cell morphology on the scaffold in the SEM image implies the cell compatibility of the scaffolds, and this was in agreement with the MTT results.…”
Section: Cytotoxicity Evaluationsupporting
confidence: 84%
See 1 more Smart Citation
“…After 14 days, the cells covered the scaffold surface and formed a tissue layer (not presented). Various studies have reported that the surface hydrophilicity serves an important role in the cell morphology on non-toxic materials, while the 24-50 degree of contact angle is a suitable range for cell attachment and proliferation (36,38). Cell morphology on the scaffold in the SEM image implies the cell compatibility of the scaffolds, and this was in agreement with the MTT results.…”
Section: Cytotoxicity Evaluationsupporting
confidence: 84%
“…The effect of the secondary bonds on the drug release pattern has been reported in previous researches. Sustained release of drugs is very important in the prolonged healing process such as tissue regeneration (36). In this manner, a drug carrier would be designed to release drug at a predetermined rate in order to maintain a constant drug concentration for a specifi c period of time with minimum side effects (37).…”
Section: Drug Release Studymentioning
confidence: 99%
“…[ 96 ] As a result, PGSp must be blended with a spinnable carrier polymer to allow non‐destructive fiber formation by electrospinning. According to its specific application ranging from soft to hard TE also including drug delivery, synthetic polymers like PCL, [ 16,19,21,29,33,38,45,97–111 ] poly(vinyl alcohol) (PVA), [ 96,112–114 ] poly(butylene succinate‐ co ‐dilinoleic succinate) PBS‐DLS, [ 115,116 ] PLA, [ 117 ] poly( l ‐lactic acid) (PLLA), [ 118,119 ] (PEO), [ 120 ] PLGA, [ 121,122 ] polyethersulfone (PSF), [ 123 ] polyhydroxybutyrate (PHB), [ 124 ] polyvinylpyrrolidone (PVP), [ 125,126 ] TPU, [ 35 ] and natural polymers like collagen, [ 127 ] gelatin, [ 128 ] fibrinogen, [ 129 ] zein, [ 130,131 ] and chitin and lignin [ 132 ] have been used for blending with PGS for successful electrospinning. Additional to blending PGS with another polymer, electrospinning of PGS within a core–shell system has been reported too where the sacrificial polymer is used as a shell which will be removed after PGS cross‐linking.…”
Section: Fabrication Techniques For Pgs‐based Biomaterialsmentioning
confidence: 99%
“…[ 97,45 ] Moreover, biomacromolecules or drugs can be loaded in PGS‐based fibers either directly by blending drugs within the fiber material and core‐shell fibers or by covalently immobilizing the drug on the final mats. [ 98,99,124,128 ]…”
Section: Fabrication Techniques For Pgs‐based Biomaterialsmentioning
confidence: 99%
“…Work on this material are advanced enough to allow for recent optimizing of the synthesis process and describing it by a mathematical equation 17 . Such a high interest is connected with the possibility to apply PGS as a cellular scaffolding in tissue engineering, 13,19‐24 a drug carrier, 8,25‐28 a surgical sealant, 29‐31 and a contact surface in biomedical sensors 32,33 …”
Section: Introductionmentioning
confidence: 99%